Comparative mutational analysis of the Zika virus genome from different geographical locations and its effect on the efficacy of Zika virus-specific neutralizing antibodies - Aziz, Abdul; Suleman, Muhammad; Shah, Abdullah; Ullah, Ata; Rashid, Farooq; Khan, Sikandar; Iqbal, Arshad; Luo, Sisi; Xie, Liji; Xie, Zhixun (Frontiers in Microbiology, 2023)
The Zika virus (ZIKV), which originated in Africa, has become a significant global health threat. It is an RNA virus that continues to mutate and accumulate multiple mutations in its genome. These genetic changes can impact the virus’s ability to infect, cause disease, spread, evade the immune system, and drug resistance. In this study genome-wide analysis of 175 ZIKV isolates deposited at the National Center for Biotechnology Information (NCBI), was carried out. The comprehensive mutational analysis of these isolates was carried out by DNASTAR and Clustal W software, which revealed 257 different substitutions at the proteome level in different proteins when compared to the reference sequence (KX369547.1). The substitutions were capsid (17/257), preM (17/257), envelope (44/257), NS1 (34/257), NS2A (30/257), NS2B (11/257), NS3 (37/257), NS4A (6/257), 2K (1/257), NS4B (15/257), and NS5 (56/257). Based on the coexisting mutational analysis, the MN025403.1 isolate from Guinea was identified as having 111 substitutions in proteins and 6 deletions. The effect of coexisting/reoccurring mutations on the structural stability of each protein was also determined by I-mutant and MUpro online servers. Furthermore, molecular docking and simulation results showed that the coexisting mutations (I317V and E393D) in Domain III (DIII) of the envelope protein enhanced the bonding network with ZIKV-specific neutralizing antibodies. This study, therefore, highlighted the rapid accumulation of different substitutions in various ZIKV proteins circulating in different geographical regions of the world. Surveillance of such mutations in the respective proteins will be helpful in the development of effective ZIKV vaccines and neutralizing antibody engineering.